DEVELOPMENT OF VOCATIONAL EDUCATION IN THE CONDITIONS OF WAR, POST-WAR RECOVERY, AND EUROPEAN INTEGRATION OF UKRAINE (Innovative professional education, 2025)
It analyzes the impact of the war on the educational infrastructure and labor market, particularly the shortage of skilled workers and the regional specifics of labor market needs. Special attention is given to Ukraine’s cooperation with EU countries in the recognition of qualifications and the adaptation of educational programs to European standards. The article identifies the prospects for vocational education development in the context of European integration processes, education seekers and professional mobility, and the adaptation of the education system to the rapidly changing labor market. The need for modernizing vocational education to ensure the preparation of highly qualified personnel capable of effectively responding to contemporary challenges and the demands of the global labor market is substantiated
Keywords: vocational education, war, post-war recovery, European integration, qualifications, mobility, labor market, EU, educational reform, adaptation of curricula